Three steps to reduction surgical site infection: presentation of a comprehensive model - Rarani, Saeid Amini; Kramer, Axel (German Medical Science GMS Publishing House, 2023)
To prevent surgical site infections (SSIs), a three-step model is proposed, which integrates perioperative measures, multidisciplinary collaboration, and continuous quality improvement (CQI) initiatives.